Epistemologi Hermeneutika Hassan Hanafi - Ahmad Solahuddin (Living Islam: Journal of Islamic Discourses, 2018)
In previous research, many scholars concern to study a Hassan Hanafi's Hermeneutic in Qur'an, although Hanafi did not write anything about Hermeneutic or Qur'anic Sciences (Ulum al-Qur'ān). These researchers aware that their research was weak and needed further research. Therefore, this research sought to continue these researches in order to welcome a new book entitled 'Science of the Qur'an' (ulum al-Qur'ān) written and published by Hassan Hanafi recently. The researcher will discover Hanafi's Hermeneutic from the epistemologicly perspective. From this research, we can conclude that the basic assumptions of the Hermeneutics of Hasan Hanafi: that a Muslim should shift their view from the al-Ḥawāmil al-Qur'āniah to the Qur'ānic spirit. Al-Ḥawāmil al-Qur'ānia are the language, the social environment, the geographic places and the historical times of the Qur'an. The Qur'ānic spirit is God's science carried by the Qur'an. The types of approaches that were in the Hassan Hanafi approach to Hermeneutic are: the objective approach or the historical approach, the subjective objectivity approach, and linguistic approach. The source of the Hermeneutics approach at Hassan Hanafi is oral narratives and codified texts.